Peak Running Velocity or Critical Speed Under Field Conditions: Which Best Predicts 5-km Running Performance in Recreational Runners? - Figueiredo, Diogo Hilgemberg; Figueiredo, Diego Hilgemberg; Manoel, Francisco de Assis; Machado, Fabiana Andrade (Frontiers in Physiology, 2021)
This study aimed to examine which variable, between the peak running velocity determined on the track field (Vpeak_TF) and critical speed (CS), is the best predictor of the 5-km running performance in recreational runners. Twenty-five males performed three tests to determine the Vpeak_TF, CS, and 5-km running performance on the track field, with a minimal interval of 48 h between each test. The Vpeak_TF protocol started with a velocity of 8 km⋅h–1, followed by an increase of 1 km⋅h–1 every 3 min until volitional exhaustion, which was controlled by sound signals, with cones at every 25 m indicating when the participants were required to pass the cone’s position to maintain the required velocity. The participants performed three time trials (TTs) (1: 2,600 m; 2: 1,800 m; and 3: 1,000 m) on the same day, with a 30-min rest period to determine the CS through the combinations of three (CS1,2,3) and two TTs (CS1,2, CS1,3, and CS2,3). The 5-km running performance time was recorded to determine the test duration, and the mean velocity (MV) was calculated. There was a significant difference observed between the Vpeak_TF and the MV 5-km running performance. However, no differences were found between the CS values and the MV 5-km running performance. A correlation was observed between the Vpeak_TF (R = −0.90), CS1,2,3 (R = −0.95), CS1,3 (R = −0.95), and the 5-km running performance time. Linear regression indicated that the Vpeak_TF (R2 = 0.82), CS1,2,3 (R2 = 0.90), and CS1,3 (R2 = 0.90) significantly predicted the 5-km running performance time. The CS results showed a higher predictive power for the 5-km running performance, slightly better than the Vpeak_TF. Also, CS1,2,3 and the CS1,3 presented the highest predictive power for the 5-km running performance of recreational runners.